Management of Immune-Related Adverse Events in Patients With Non-Small Cell Lung Cancer - Burke, Michael; Rashdan, Sawsan (Frontiers in Oncology, 2021)
With proven efficacy of the use of immunotherapy in almost all stages of NSCLC, immunotherapy toxicity has become a very important topic that requires immediate recognition and management. The diagnosis of toxicities associated with immunotherapy in lung cancer can be very challenging and often requires multidisciplinary effort. This mini review gives an overview of the diagnosis and management of immune-related adverse events that arise from using immunotherapy in NSCLC, as well as the potential biomarkers for its early identification and future directions.